Monocyte activity in Behcet's disease - (:unkn) unknown (OXFORD UNIV PRESS, 1996)
Monocytes obtained from patients with Behcet's disease (BD) were examined for differentiation markers (expression of CD14 and antigens reacting with monoclonal antibodies 25F9 and G16/1) and for expression of selected adhesion molecules. There was significantly raised expression of the CD14 molecule, and increased staining with 25F9 and G16/1 antibodies in monocytes obtained from patients with ED. A monocyte activation marker, soluble CD14, was also found to be raised in patients' serum compared with normal serum (8.1 +/- 9.2 vs 1.4 +/- 0.7 mu g/ml). Furthermore, BD patients' monocyte culture supernatants caused significantly increased adhesion of normal neutrophils to endothelial cell monolayers in vitro. All these findings show that BD patients' monocytes are active in vivo and produce a number of pro-inflammatory cytokines which may play a role in the chronic inflammation found in these patients.
Keywords: monocyte; Behcet's disease; adhesion molecules; NECROSIS-FACTOR-ALPHA; HUMAN ENDOTHELIAL-CELLS; MACROPHAGES; CD14; LIPOPOLYSACCHARIDE; GENERATION; ACTIVATION; ADHERENCE; RECEPTOR; ADHESION